1981
DOI: 10.1128/iai.32.1.251-259.1981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Essential Amino Acid Limitations upon the Susceptibility to Salmonella typhimurium and the Effect Upon Humoral and Cellular Immune Responses in Mice

Abstract: We investigated the effects of dietary essential amino acid limitations on the susceptibility of mice to Salmonella typhimurium infections and on humoral and cellular immune (cell-mediated immune) responses of mice. Mice fed synthetic diets limited (significantly less than optimum concentration) in a single essential amino acid (leucine, isoleucine, valine, or lysine) for 3 weeks after they were weaned exhibited significantly enhanced susceptibility to S. typhimurium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 25 publications
1
24
1
Order By: Relevance
“…The results obtained in this study are in disagreement with the generally reported observations that protein malnutrition enhances host susceptibility to various bacterial infections (6), such as Salmonella infections (14). However our results confirm those reported by other investigators for S. typhimurium (15) and other bacteria (7,9,20), showing increased resistance of hypoferremic animals to bacterial infection.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…The results obtained in this study are in disagreement with the generally reported observations that protein malnutrition enhances host susceptibility to various bacterial infections (6), such as Salmonella infections (14). However our results confirm those reported by other investigators for S. typhimurium (15) and other bacteria (7,9,20), showing increased resistance of hypoferremic animals to bacterial infection.…”
Section: Discussioncontrasting
confidence: 81%
“…However our results confirm those reported by other investigators for S. typhimurium (15) and other bacteria (7,9,20), showing increased resistance of hypoferremic animals to bacterial infection. Generally, protein malnutrition increases host susceptibility to infection as a result of the depression of nonspecific resistance factors and alteration of humoral and cellmediated immunity (6,13,14). Surprisingly the results described here demonstrated that CBA/CA mice fed a low-protein diet (containing 4% proteins) were more resistant to S. typhimurium C5 infection than mice fed a protein-sufficient diet (containing 17% proteins).…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Focusing on health status, protective immune responses also require supply of nutrients in suitable time and amount (Humphrey et al, 2002), whereas deficiency in some nutrients can cause disease or make animals more susceptible to infectious and non-infectious diseases. In mammals, many investigators have reported that deficiency or excess of protein or specific essential amino acids have changed several immune responses such as antibody titre and number of plaque-forming cells against selected antigens (Gershoff et al 1968;Kenney et al, 1968Kenney et al, , 1970Bounous and Kongshavn, 1978;Lotan et al 1980), lymphocyte proliferative response to mitogens (Barbul et al 1980;Petro and Bhattacharjee 1981;Nauss et al, 1982), delayed-type hypersensitivity response (Bounous and Kongshavn, 1978) and allograft rejection (Lotan et al 1980). In avian species, it has been shown that deficiency or excess of dietary protein (Glick et al 1981(Glick et al , 1983Payne et al, 1990) or amino acids (Bhargava et al 1970, Bhargava et al, 1971Tsiagbe et al, 1987a,b) also altered immune responses.…”
Section: Introductionmentioning
confidence: 99%